1994
DOI: 10.1200/jco.1994.12.11.2309
|View full text |Cite
|
Sign up to set email alerts
|

Squamous cell carcinoma antigen: prognostic significance and role in the monitoring of neoadjuvant chemotherapy response in cervical cancer.

Abstract: Our data show that SCC assay may provide useful information to improve the prognostic characterization and disease monitoring of patients with locally advanced cervical cancer undergoing neoadjuvant chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
79
3

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(92 citation statements)
references
References 19 publications
7
79
3
Order By: Relevance
“…Persistently elevated and/or increasing serum SCC concentrations after treatment suggest tumor persistence or progressive disease (387,398,399,408,(412)(413)(414)428 ). In 1 study, CEA and SCC marker concentrations measured 1 month after primary treatment with chemoradiation were better than pretreatment serum concentrations in predicting clinical outcome (413 ).…”
Section: Use Of Scc In Monitoring Response To Treatment and Early Detmentioning
confidence: 85%
See 2 more Smart Citations
“…Persistently elevated and/or increasing serum SCC concentrations after treatment suggest tumor persistence or progressive disease (387,398,399,408,(412)(413)(414)428 ). In 1 study, CEA and SCC marker concentrations measured 1 month after primary treatment with chemoradiation were better than pretreatment serum concentrations in predicting clinical outcome (413 ).…”
Section: Use Of Scc In Monitoring Response To Treatment and Early Detmentioning
confidence: 85%
“…Another group found that SCC and CA 125, in addition to stage, were significantly related to survival in the multivariate analysis of 142 patients with cervical cancer ranging from stage IA through IVB (385 ). It was concluded from a multivariate analysis of 102 women with locally advanced squamous cell cancer or adenocarcinoma of the cervix that an SCC concentration greater than 5 g/L was an independent predictor of response to neoadjuvant chemotherapy and poor survival (408 ). A pretreatment SCC concentration greater than 10 g/L (but not between 2 and 10 g/L) had a significant impact on survival in a multivariate analysis in 401 patients with stage I to IVA squamous cell cervical cancer, primarily treated with radiotherapy (399 ).…”
Section: Nacb Cervical Cancer Panel Recommendation 2: Serum Scc Concementioning
confidence: 99%
See 1 more Smart Citation
“…Pretreatment SCC levels correlate with cellular differentiation, tumour stage and volume, lymph node status and blood vessel invasion (Reynolds et al, 2005). However, there are conflicting reports on the prognostic significance of pretreatment SCC measurements (Scambia et al, 1994;Gaarenstroom et al, 1995;Duk et al, 1996;Ngan et al, 1996;Bolger et al, 1997;Hong et al 1998). In addition, there are no useful markers in cervical adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Lacking reliable clinical predictive factors, some authors tested chemotherapy resistance by assessing biochemical factors such as serum levels of squamous cell carcinoma antigen [12], microvessel density [6,7], oncogenes and tumor suppressor genes [13], and cyclooxygenase-2 [8]. Anemia is the most frequently observed hematological abnormality factor among cancer patients.…”
Section: Discussionmentioning
confidence: 99%